Maghemite based silicone composite for arterial embolization hyperthermia - Smolkova, Ilona S; Kazantseva, Natalia E; Makoveckaya, Kira N; Smolka, Petr; Saha, Petr; Granov, Anatoly M (Materials science & engineering. C, Materials for biological applications, 2015)
Maghemite nanoparticle based silicone composite for application in arterial embolization hyperthermia is developed. It possesses embolization ability, high heating efficiency in alternating magnetic fields and radiopaque property. The initial components of the composite are selected so that the material stays liquid for 20min, providing the opportunity for transcatheter transportation and filling of the tumour vascular system. After this induction period the viscosity increases rapidly and soft embolus is formed which is able to occlude the tumour blood vessels. The composite is thermally stable up to 225°C, displays rubber-elastic properties and has a thermal expansion coefficient higher than that of blood. Maghemite nanoparticles uniformly distributed in the composite provide its rapid heating (tens of °Cmin(-1)) due to Neel magnetization relaxation. Required X-ray contrast of composite is achieved by addition of potassium iodide.
Keywords: železité sloučeniny; Hyperthermia, Induced; jodid draselný; Ferric Compounds; magnetické pole; Embolization, Therapeutic; nanokompozity; indukovaná hypertermie; Nanocomposites; pružnost; Animals; lidé; Humans; zvířata; Magnetic Fields; Elasticity; Potassium Iodide; silikony; terapeutická embolizace; Silicones